2017
DOI: 10.4314/jasem.v21i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Species and prevalence determination of Human Intestinal Parasites among Patients attending two Medical Centers in Yola, Adamawa State, Nigeria

Abstract: ABSTRACT:Intestinal parasitic infections constitute a global health burden causing clinical morbidity. Parasitic protozoa and helminthes are responsible for some of the most devastating and prevalent diseases of human. The study was conducted to determine the prevalence of intestinal parasites among patients attending Federal Medical Center and Specialist Hospital Yola. A total of 438 stool specimens was collected randomly from the patients (204 male and 234 female) and examined by saline wet mount procedure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The Upper Benue Trough in the Adamawa State of northeastern Nigeria is one of the major pastoralist activity centres in Nigeria. Although a few studies have separately evaluated zoonotic diseases among livestock [17] and humans [18] around the Upper Benue Trough, none has reported on concurrent zoonotic diseases or pathogens among humans, animals and/or the environment in the Upper Benue Trough. Documentation of the zoonotic enteric parasite (ZEP) distribution, which included Entamoba spp., Cryptosporidium spp., Giardia intestinalis, Fasciola spp., Taenia spp., and Trichostrongylus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The Upper Benue Trough in the Adamawa State of northeastern Nigeria is one of the major pastoralist activity centres in Nigeria. Although a few studies have separately evaluated zoonotic diseases among livestock [17] and humans [18] around the Upper Benue Trough, none has reported on concurrent zoonotic diseases or pathogens among humans, animals and/or the environment in the Upper Benue Trough. Documentation of the zoonotic enteric parasite (ZEP) distribution, which included Entamoba spp., Cryptosporidium spp., Giardia intestinalis, Fasciola spp., Taenia spp., and Trichostrongylus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we reported Fasciola hepatica from samples obtained from three local government/towns (Ganye, Jada and Toungo) in Southern senatorial zone and one (Hong) in Central senatorial zone. Fasciolosis has been reported among patients attending two medical centers in Yola, Adamawa state [29], however the identification of Fasciola hepatica from apparently healthy subjects from five local governments underscores the importance of this fluke as an emerging parasite.…”
Section: Plate 1 F Hepaticamentioning
confidence: 99%
“…Although the prevalence were low, it could increase if adequate measures to mitigate spread of these emerging parasites are not put in place. Studies have reported a higher prevalence of Fasciola spp in Bauchi, Yola and Zaria[28,29,30], however Paragonimus spp and Schistosoma intercalatum parasites have been rare reported in the Northern part of Nigeria.…”
mentioning
confidence: 99%